Implementation of National Police Chief Regulation No. 8/2018 on Divorce Settlement for Police Members in Lampung Regional Police Environment - Budi, Indra Setia (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study discusses the effectiveness of the implementation of National Police Chief Regulation No. 8/2018 concerning divorce permission and mediation in the Police environment, especially in the Lampung Regional Police. The main problems studied are the application of divorce permits, obstacles in the mediation process, and their contribution to the renewal of Islamic family law in Indonesia. The research used a qualitative approach with field research methods through in-depth interviews, documentation, and triangulation data analysis. The findings show that mediation can reduce the divorce rate, although there are obstacles such as time constraints and conflicts in the roles of police officers. The conclusion states that the mediation policy plays an important role in maintaining the stability of the family and the police institution, but a clear indicator standard is needed for divorce decisions. The research recommends evaluating and improving the relevant regulations to be more in line with the Marriage Law and the Compilation of Islamic Law, to ensure transparency and legal certainty in the divorce process within the Polri.Keywords: Divorce Msediation, National Police Chief Regulation No. 8/2018, Islamic Family Law